Analysis of the determinants of exporting intensity in the field of innovation - Vanessa Suárez-Porto; Manuel Guisado-González (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2014)
From a sample of Spanish manufacturing businesses, extracted from the 2005 Technological Innovation Panel (PITEC 2005), we suggest a lineal regression model in which we relate the exporting intensity with the product innovation, the process innovation, the sectorial technological intensity, the business extent and the membership to a pool of businesses. In the descriptive and statistical analysis, we obtained that all of these variables have a positive and significant influence on the exporting intensity. Regarding this matter, we have checked that the main influence corresponds to businesses that develop product innovation strategies, are of medium extent, are assigned to sectors of medium-high technological intensity and belong to a foreign corporate group.
Keywords: M16; 330; Exporting intensity; Innovation; Technological Intensity